Public policies, social inclusion and democratic development - Salgado, Eneida Desiree (Universidad Nacional del Litoral, 2015)
The following essay portrays public policies as a form of accomplishing social duties to allow public participation, not only in its genesis, but also in throughout the process of its execution. Furthermore, it examines the Information Access Act as an instrument to guarantee the fundamental right, with the specific aim of intervening in the public debate. Moreover, the present thesis discusses the issue of access to access from the perspective of public policies of digital inclusion.